(untitled) - Zarnay, Pavel (Doprava a spoje, 2012)
``The Strategy of the European Union for the Danube area'' (the Danube strategy) is a comprehensive strategic programme, covering and linking several regional policies with a view to arriving at a common procedure in the framework of the European territory of the Danube basin. Its principle is the cooperation of individual countries on the basis of their own action plans incorporated into one common programme adopted. The primary objective of the cooperation is to develop mobility and thereby also the Joint Danube region marketing potential. A secondary aim of the strategy is to use as a resource for the larger Danube transport mainline and the opening of the European Union. The path to the realization of the objectives of the revision of the operational programme Transport leads through.